The Transformation of Italian Communism - Amyot, Grant (Labour / Le Travail, 1997)
The article reviews the book, "The Transformation of Italian Communism," by Leonard Weinberg.
Keywords: BOOKS -- Reviews; Communism; ITALY; Nonfiction; TRANSFORMATION of Italian Communism, The (Book); WEINBERG, Leonard